Identification of retina image size in relation to electrooculography signal - Tumari, S. Z. M. (IEEE, 2012)
The aim of this study is to identify retina image size relation to Electrooculography signal. USB Digital Microscope is the process to find the diameter pupil. Other than that, EEG machine Neurofax 9200 was used to acquire the EOG signal acquisition when eye move up, down, right and left. MATLAB is used to analyze the image and measure the diameter of pupil image and implement the signal acquisition that presented in the EEG machine. The image was lay emphasis on their edges, therefore easier to realize with our naked eyes. The nature of the sharpening is prejudiced by the blurring radius using difference pixel. Several approaches have been substantiated to measure the diameter of pupil such as edge detection, active contour, binarization and others. Aiming at the signal acquisition the methods that being used is Second Order Butterworth filter and frequency domain. The visual effects to form image appear sharper, the original image which is in RGB or true color that comprise a lot of noise was produced by program design using MATLAB. Base on both results, the relation between size of pupil and EOG signal can be obtained and identified.